Prognostic stratification of patients with AJCC 2018 pStage IVB oral cavity cancer: Should pT4b and pN3 disease be reclassified?. (August 2021) - Kang, Chung-Jan; Tsai, Chi-Ying; Lee, Li-Yu; Lin, Chien-Yu; Yang, Lan-Yan; Cheng, Nai-Ming; Hsueh, Chuen; Fan, Kang-Hsing; Wang, Hung-Ming; Hsieh, Chia-Hsun; Ng, Shu-Hang; Yeh, Chih-Hua; et al.
Highlights: Stage IVB OCSCC is defined as either pT4b or pN3 disease. The 5-year outcomes of pT4a and pT4b tumors are similar. The prognosis of pT3-4N3b is less favorable than that of pT1-2N3b disease. pT4bN0-2 and pT1-2N3b should be downstaged from pStage IVB to IVA. The newly proposed pStage IV improves prognostic stratification. Abstract: Objectives: pStage IVB oral cavity squamous cell carcinoma (OCSCC) is defined as either pT4b or pN3 disease. We sought to devise an improved prognostic stratification of this patient group. Methods: Between December 2003 and January 2018, we retrospectively reviewed the clinical records of 1331 consecutive patients with OCSCC who received tumor excision and neck dissection. The number of patients with pT4a/pT4b, pT1N3b/pT2N3b/pT3N3b/pT4N3b, and pStage IVA/IVB was 370/83, 3/49/42/142, and 332/295, respectively. Results: The 5-year rates of disease-free survival (DFS) and disease-specific survival (DSS) for patients with pT4a/pT4b disease were 64%/63% ( p  = 0.973) and 72%/69% ( p  = 0.672), respectively. The 5-year DFS and DSS rates for patients with pT1N3b/pT2N3b/pT3N3b/pT4N3b disease were 67%/65%/40%/42% ( p  < 0.001; pT1-2N3b versus pT3-4N3b, p  = 0.002) and 100%/68%/45%/49% ( p  < 0.001; pT1-2N3b versus pT3-4N3b, p  = 0.002), respectively. We devised a new definition for pStage IV by considering patients with pT4bN0-2 and pT1-2N3b diseases as pStage-IVA. The number of patients with pStage IVA/IVB (pT3-4N3b) was 443/184. The 5-year rates of AJCC pStage IVA/IVB and the newly proposed pStage IVA/IVB (pT3-4N3b) were as follows: DFS, 74%/52% and 72%/42%; DSS, 83%/58% and 81%/47%; respectively, all p value < 0.001. Conclusions: The clinical outcomes of pT4b and pT4a OCSCC are similar. However, patients with pT3-4N3b disease have a less favorable 5-year prognosis compared with cases with pT1-2N3b. In light of the unfavorable outcomes, pT3-4N3b disease should continue to be classified as pStage IVB. Conversely, pT4bN0-2 and pT1-2N3b diseases portend a less adverse prognosis and should therefore be downstaged to pStage IVA.